The riddle : form and performance - Kaivola-Bregenhøj A (Switzerland, 2022)
The article concentrates on the true or the ordinary riddle, which is the best-known of the old riddles. True riddles consist of two parts, one functioning as a question, the other as an answer. In riddling the answerer or riddlee tries to find an acceptable answer to the question. Sometimes riddlees are deliberately misled because the “right” answer is completely unexpected. Riddles are “texts” only in archives and publications; in the field, they are always oral lore closely tied to their performing context. Study of social and cultural contexts is a new part of riddle research. Field researchers’ studies and findings are important. The article includes riddle definitions and analysis of subjects, metaphors and formulae of riddles as well as the functions of riddling. New challenges are the driving force behind research. I attempt to find something new in my material. New for me has been discovering the humour in riddles. Reading dozens and even hundreds of riddle variants begins to give me some idea of the fun and humour inherent in riddles. There are still questions in riddle materials waiting to be asked; it is always possible to discover something new. View Full-Text
Keywords: answer; definition; formula; function; joking question; metaphor; riddle; riddling; true riddle